Representasi Perempuan Jawa Dalam Novel Bumi Manusia Dan Pengakuan Pariyem - Indah Fadhilla; Anwar Ilma (Jurnal Inovasi dan Kreativitas (JIKa), 2023)
Abstract Problems: The image of society in literary works reflects the image of society in everyday life. To understand the community in the text, we can look at the semiotic signs in the storytelling elements. In the stories Bumi Manusia and Pengakuan Pariyem, there are depictions of female characters under the power of employers. Despite having the same conditions, there are differences in the representation of Javanese women in the two stories. Purpose: This study aims to determine the representation of Javanese women in the stories Bumi Manusia and Pengakuan Pariyem. Methodology: This study uses qualitative research methods using descriptive analysis. Data collection in this study was carried out using documentation techniques for passages in the text to find semiotic signs in the story. The quotations were analyzed using the representation theory from Stuart Hall. Results/Findings: This study found differences in the depiction of Javanese women in the stories Bumi Manusia and Pengakuan Pariyem, especially those depicted by Javanese women under the power of their masters. In the story, Pengakuan Pariyem, the character under the employer's control is Pariyem, while in the story Bumi Manusia, it is Nyai Ontosoroh. The figure of Nyai Ontosoroh is represented as a Javanese woman who can blend in with European culture. In contrast, Pariyem is represented as a Javanese woman who respects local culture. These two figures have in common that they are both represented as intelligent Javanese women. Paper Type: descriptive qualitative research Keywords: Representation; Javanese Woman, Bumi Manusia, Pengakuan Pariyen